2008
DOI: 10.1093/oxrep/grn026
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants and welfare programmes: exploring the interactions between immigrant characteristics, immigrant welfare dependence, and welfare policy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 16 publications
3
83
0
Order By: Relevance
“…2 1 For a broad review of the literature on immigration and welfare, see Barrett and McCarthy (2008). 2 In conducting this analysis, we are updating work by Brücker et al (2002) in which data from 1996 to 1998 was used.…”
Section: Onmentioning
confidence: 99%
“…2 1 For a broad review of the literature on immigration and welfare, see Barrett and McCarthy (2008). 2 In conducting this analysis, we are updating work by Brücker et al (2002) in which data from 1996 to 1998 was used.…”
Section: Onmentioning
confidence: 99%
“…Bratsberg, Raaum, and Roed (2007) show that migrants in Norway are net users of the welfare state, with adverse consequences on their labour market performance. A very different finding is documented in Barrett and McCarthy (2008) and Barrett and McCarthy (2007) for Ireland, where it is shown that, after controlling for a large set of observable characteristics, migrants use the welfare state significantly less than natives.…”
Section: Introductionmentioning
confidence: 81%
“…It is in their personal interest to limit the number of competitors in the labor market and the welfare state (Malchow-Moller et al 2008). Migrants compete particularly with economically vulnerable natives in the labor market as well as in the realm of the welfare state, because compared to natives they have lower labor market resources and a stronger dependency on welfare benefits (Brücker et al 2002;Barret and McCarthy 2008). Hence, economically vulnerable natives may support restrictive immigration policies because they think that immigration deteriorates their economic opportunities and entitlements.…”
Section: Individual Differences In Support For Restrictive Immigratiomentioning
confidence: 99%